2010
DOI: 10.1017/s0021932009990575
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Relationship Power in Couple Decisions About Contraception in the Us

Abstract: Most analyses of the contraceptive decision making in which couples engage are based on the reports of only one partner, usually the female partner. This study uses information from the 2006 National Couples Survey that was obtained from both partners in intimate heterosexual relationships to investigate the relative impact of the male and female partner’s method preferences on the type of method they use together. It also investigates the extent to which differences in power between the partners, measured on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 37 publications
(49 reference statements)
5
63
0
1
Order By: Relevance
“…As for resources and contraception, the relationship between gender identities and contraceptive practice proves to be ambiguous. On the one hand, contraception is often perceived as a female sphere of influence because women bear the physical costs of pregnancy and birth, and are traditionally responsible for childcare (Grady et al 2010, Thomson 1997. Although women can feel compelled to take responsibility for contraception as part of their female role, others suggest that women engage in 'contraceptive gatekeeping' and that they report a clear preference for being primarily in charge of contraception (Fennell 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As for resources and contraception, the relationship between gender identities and contraceptive practice proves to be ambiguous. On the one hand, contraception is often perceived as a female sphere of influence because women bear the physical costs of pregnancy and birth, and are traditionally responsible for childcare (Grady et al 2010, Thomson 1997. Although women can feel compelled to take responsibility for contraception as part of their female role, others suggest that women engage in 'contraceptive gatekeeping' and that they report a clear preference for being primarily in charge of contraception (Fennell 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as fertility care involves women and men, male partner opinions could also influence the choice of a FP method [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only limited attention has been paid to reproductive choices, and more specifically contraceptive use, as a possible outcome of couples' power balance (Grady et al, 2010) but a number of scholars does focus on the influence of partner differentials on couples' contraceptive use. Two types of studies can be identified.…”
Section: Previous Research On the Link Between Power And Couples' Conmentioning
confidence: 99%
“…Grady et al, 2010;Kusunoki and Upchurch, 2011;Manning et al, 2009;Stolley, 1996), research on the social determinants of contraceptive use has mainly studied the female population, because reproduction and contraception are often framed as a female sphere of influence (Edwards, 1994;Fennell, 2011). Moreover, the majority of studies, also those that have taken men's as well as women's preferences and childbearing desires into account, have limited their attention to individual demographic characteristics, such as the influence of educational attainment or income level on the adoption of certain contraceptive methods (Anderson et al, 2012;Martinez et al, 2006;Moreau et al, 2006;Mosher and Jones, 2010;Oddens et al, 1994aOddens et al, , 1994bSpinelli et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation